PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. RAMAYANA LESTARI SENTOSA, Tbk CABANG MAKASSAR R70 - Megawhati Artiyany; Lina Mariana (Journal of Social Sustainability Management, 2022)
The purpose of this study was to determine the competence and compensation for the performance of the employees of PT. Ramayana Lestari Sentosa, Tbk (R70) Makassar Branch. The types of data used in this research are primary data and secondary data. The analytical method used is the statistical analysis method in the form of multiple regression analysis, correlation coefficient, determination coefficient as well as t-test and f-test.The results of this study indicate that competence and compensation partially or simultaneously have a significant positive effect on employee performance at PT. Ramayana Lestari Sentosa, Tbk (R70) Makassar Branch.